A high-spin nickel(ii) borohydride complex in dehalogenation. Issue 1 (8th December 2015) - Tak, Hyeonwoo; Lee, Hyunjoo; Kang, Joongoo; Cho, Jaeheung
Abstract : A mononuclear high-spin (η 2 -BH4 ) nickel(ii ) complex bearing a macrocyclic tridentate N-donor ligand was prepared and its reactivity was investigated in dehalogenation reactions. Abstract : A nickel(ii )–borohydride complex bearing a macrocyclic tridentate N-donor ligand, [Ni(Me3 -TACN)(BH4 )(CH3 CN)] + (Me3 -TACN = 1, 4, 7-trimethyl-1, 4, 7-triazacyclononane), was prepared, isolated, and characterized by various physicochemical methods, including UV-vis, ESI-MS, IR and X-ray analyses. The structural and spectroscopic characterization clearly shows that the borohydride ligand is bound to the high-spin nickel(ii ) center in an η 2 -manner. Density functional theory calculations provided geometric information of2, showing that the η 2 -binding of borohydride to the nickel center is more favorable than the η 3 -binding mode in CH3 CN. The complex is paramagnetic with an effective magnetic moment of 2.9 μ B consistent with a d 8 high-spin system. The reactivity of the high-spin nickel(ii )–borohydride complex was examined in dehalogenation with numerous halocarbons. A kinetic isotope effect value of 1.7 was observed in the dehalogenation of CHCl3 by the nickel(ii )–borohydride complex. Kinetic studies and isotopic labeling experiments implicate that hydride ion or hydrogen atom transfer from the borohydride group is the rate determining step. The positive Hammett ρ value of 1.2, obtained in the reactions of [Ni(Me3 -TACN)(BH4 )(CH3 CN)] + and para -substituted benzoyl chloride, indicates that the dehalogenation by the nickel(ii )–borohydride species occurs via a nucleophilic reaction.